All‐Solid‐State Flexible Asymmetric Supercapacitors Fabricated by the Binder‐Free Hydrophilic Carbon Cloth@MnO2 and Hydrophilic Carbon Cloth@Polypyrrole Electrodes. (3rd January 2019) - Chen, Zhiyuan; Zheng, Luyao; Zhu, Tao; Ma, Zhihao; Yang, Yongrui; Wei, Chunding; Liu, Lei; Gong, Xiong
Abstract: Supercapacitors have attracted enormous attention for energy storage in both academic and industrial sectors in the past years. In this study, all‐solid‐state flexible asymmetric supercapacitors (ASCs) without any binder, incorporated with the hydrophilic carbon cloth (HCC) with MnO2 nanocomposite (HCC@MnO2 ) as the positive electrode, the HCC with polypyrrole (PPy) (HCC@PPy) as the negative electrode, and polyvinyl alcohol (PVA)–LiCl gel as both gel electrolyte and separator, are reported. The HCC@MnO2 and HCC@PPy electrodes are prepared by direct deposition of either MnO2 nanoparticles or PPy nanofilms on the HCC through a simple, facile, and controllable electrochemical deposition method, respectively. The HCC@MnO2 and HCC@PPy electrodes provide rich contact area for gel electrolyte, facilitating the rapid delivery of electrolyte ions, and also minimize the resistance of ASCs. As a result, all‐solid‐state flexible binder‐free HCC@MnO2 //HCC@PPy ASCs exhibit a large operating voltage of 1.8 V, high energy density of 28.2 Wh kg −1 at the power density of 420.5 W kg −1, and excellent cycling stability (91.2% capacitance retention after 5000 cycles). The present study provides a facile, scalable, and efficient approach to fabricate all‐solid‐state ASCs with high electrochemical storage performance for flexible electronics. Abstract : Large operating voltage, high energy density, and excellent cycling stability are observed from novel all‐solid‐state flexible asymmetric supercapacitors incorporated with the hydrophilic carbon cloths (HCCs) within MnO2 as the positive electrode and the HCCs within polypyrrole as the negative electrode, and with poly(vinyl alcohol)–LiCl gels as both electrolyte and separator.